Biomechanical aspects of segmented arch mechanics combined with power arm for controlled anterior tooth movement: A three-dimensional finite element study - Ozaki, Hiroya (J Dent Biomech, 2015)
The porpose of this study was to determine the optimal length of power arms for achieving controlled anterior tooth movement in segmented arch mechanics combined with power arm. A three-dimensional finite element method was applied for the simulation of en masse anterior tooth retraction in segmented power arm mechanics. The type of tooth movement, namely, the location of center of rotation of the maxillary central incisor in association with power arm length, was calculated after the retraction force was applied. When a 0.017 × 0.022-in archwire was inserted into the 0.018-in slot bracket, bodily movement was obtained at 9.1 mm length of power arm, namely, at the level of 1.8 mm above the center of resistance. In case a 0.018 × 0.025-in full-size archwire was used, bodily movement of the tooth was produced at the power arm length of 7.0 mm, namely, at the level of 0.3 mm below the center of resistance. Segmented arch mechanics required shorter length of power arms for achieving any type of controlled anterior tooth movement as compared to sliding mechanics. Therefore, this space closing mechanics could be widely applied even for the patients whose gingivobuccal fold is shallow. The segmented arch mechanics combined with power arm could provide higher amount of moment-to-force ratio sufficient for controlled anterior tooth movement without generating friction, and vertical forces when applying retraction force parallel to the occlusal plane. It is, therefore, considered that the segmented power arm mechanics has a simple appliance design and allows more efficient and controllable tooth movement.